Time dependent decomposition of ammonia borane for the controlled production of 2D hexagonal boron nitride - Babenko, V; Lane, G; Koos, A; Murdock, A; So, K; Britton, J; Meysami, S; Moffat, J; Grobert, N (Nature Publishing Group, 2017)
Ammonia borane (AB) is among the most promising precursors for the large-scale synthesis of hexagonal boron nitride (h-BN) by chemical vapour deposition (CVD). Its non-toxic and non-flammable properties make AB particularly attractive for industry. AB decomposition under CVD conditions, however, is complex and hence has hindered tailored h-BN production and its exploitation. To overcome this challenge, we report in-depth decomposition studies of AB under industrially safe growth conditions. In situ mass spectrometry revealed a time and temperature-dependent release of a plethora of NxBy-containing species and, as a result, significant changes of the N:B ratio during h-BN synthesis. Such fluctuations strongly influence the formation and morphology of 2D h-BN. By means of in situ gas monitoring and regulating the precursor temperature over time we achieve uniform release of volatile chemical species over many hours for the first time, paving the way towards the controlled, industrially viable production of h-BN.